Cechy polskiego języka biznesu jako języka specjalistycznego w początkowym etapie kształtowania się (na podstawie „Czasu” z lat 1870–1914) - Gajda, Paulina (Investigationes Linguisticae, 2016)
The aim of the article is to present a specific features of business language at the initial stage of its development (years: 1870-1914). This stage provides an interesting research material and its analysis is necessary to have a full overview of business language as a specialized variety of contemporary Polish. The article concerns various aspects of this issue: diversity of business subject fields, the primacy of cognitive function over the communicative function and specific features of the grammatical and lexical scope. All features stem from the specific communicative situations in which business language as a language for specific purposes occurs. The analysis embraces the linguistic material that comes from the Krakow newspaper Czas.